Morphology of Sigmoid Colon in South Indian Population: A Cadaveric Study - Stelin Agnes Michael; Suganthy Rabi (Journal of Clinical and Diagnostic Research, 2015)
Introduction: Sigmoid volvulus is a common etiological factor in acute large bowel obstruction. The increased length of sigmoid colon is attributed as one of the causes of sigmoid volvulus. Aim: The aim of this study was to find the morphology of sigmoid colon in South Indian population using cadavers. Materials and Methods: The present study was performed with 31 cadavers used for teaching purpose. The sigmoid colon was classified into classical, long-narrow and long- broad types by their disposition in the abdominal cavity. The sigmoid loop’s relation to pelvic brim was also observed and grouped as pelvic and suprapelvic in position. The length of sigmoid colon along the mesenteric and antimesenteric border, height and width of sigmoid mesocolon in relation to the pelvic brim and the root of mesentery were measured in the study. Results: The study showed that the majority of the sigmoid colons fell into the classical type (47.6%). The sigmoid colon in pelvic position was significantly more prevalent. The mean length of sigmoid colon was 15.2 ± 4.4cm and 19.2 ± 6cm considering the pelvic brim and root of mesentery as reference points of measurement respectively. The mean length along antimesenteric border was 22.3 ± 7.9cm and 25 ± 8.7cm along the same reference points. The mean length of mesocolon height was 6.5 ± 3cm with reference to pelvic brim and 7.3 ± 3cm with reference to root of Sigmoid mesocolon respectively. The mean width of mesocolon was 7.4 ± 3cm (pelvic brim) and 8 ± 2cm (root of Sigmoid mesocolon) There was a positive correlation of sigmoid colon length with the height of the mesocolon. The gender analysis showed that males had statistically significant longer sigmoid colon and mesocolon. Conclusion: This study documents that the South Indian population has a more classical type of sigmoid colon and that the anatomical dimensions of sigmoid colon and its mesocolon is significantly longer in males.